Argentum Potorium in Romano-Campanian Wall-Painting - Tamm, John A. (My University, 2001)
The first centuries BC and AD encompassed the first great period of Roman silverware production. Wall-paintings, surviving pieces, and textual references all testify to the importance of silverware, in particular the silver vessels and implements used in the preparation, service, and drinking of wine, during this period. Besides the functional aspects, possession of silverware served also as an indicator of one's wealth and status. In a number of wall-paintings with banqueting or related themes, primarily from Campania but also from Rome, silverware plays a prominent role. The painted vessels are often viewed, by modern scholars, as representative of the kinds of vessels then current in the Roman world, as if the painters were using actual pieces for models. This provides the point of departure for this dissertation, a detailed study of drinking silver in Romano-Campanian wall-painting. Such a study reveals more than just whether or not the painters were closely copying actual vessels; it is, in fact, argued here that such copying was not part of their usual procedure. The paintings also reveal what kinds of vessels were considered relevant in a banqueting context, and at times, how these vessels were used. Other areas onto which the paintings cast light include the working methods in general of the painters, the question of prototypes and their possible contents, and the role of the patron. The paintings studied in this dissertation cannot be divorced from Roman wall-paintings as a whole. The conclusions drawn here, therefore, have relevance for all Roman wall-paintings and, to some degree, for Roman art in general.
Keywords: Argentum Potorium; Romano-Campanian Wall-Painting